Homebuilding and woodworking in colonial America - Wilbur, C. Keith, 1923- (Philadelphia, Pa. : Chelsea House, 1997)
Illustrations and text provide information about seventeenth and eighteenth-century construction techniques and tools, discussing every aspect of home building, from choosing trees to finishing work.
Includes bibliographical references (p. [115]-116) and index.
Young Adult
Keywords: Building, Wooden -- United States -- History -- 16th century; Carpentry -- United States -- History -- 16th century; House construction -- United States -- History -- 16th century; Buildings -- History; Carpentry -- History; House construction -- History